Artificial intelligence and automated decision making under the GDPR and the POPIA - Goldman, Gavin David (University of the Witwatersrand, Johannesburg, 2024)
This analysis considers the concepts of AI and machine learning and examines their reliance on the processing of personal data and the challenges this poses from a data- privacy and human-rights perspective, particularly in relation to profiling. It evaluates the effectiveness of the General Data Protection Regulation (GDPR) and the Promotion of Personal Information Act 4 of 2013 (POPIA) in regulating Automated Decision Making (ADM) and considers the limitations of the right to an explanation under these provisions. The analysis proposes that the current framework of the GDPR and POPIA does not clearly address the issue of explainability and that the focus should shift to providing a data subject with a counterfactual to give practical effect to this right which would better serve data subjects
A research report Submitted in partial fulfillment of the requirements for the degree of Master of Laws by Coursework and Research Report, School of Laws, University of the Witwatersrand, Johannesburg 2024
Keywords: Artificial intelligence; GDPR; POPIA; UCTD; SDG-9: Industry, innovation and infrastructure